Comparison of shid and wagner wound classifications for assessing quality of life in patients with diabetic foot ulcers - Suriadi, Suriadi; Haryanto, Haryanto; Anggreni, Patricia Dini Ayu (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Diabetic Foot Ulcer (DFU) is a chronic complication of diabetes mellitus that significantly affects patients’ quality of life. Several wound classification systems are used to assess DFU severity, including the Wagner and SHID classifications. However, evidence comparing the application of these classifications in evaluating quality of life (QoL) among DFU patients has not been comprehensively mapped. Purpose: To map and compare existing evidence regarding the use of SHID and Wagner wound classifications in evaluating quality of life in patients with diabetic foot ulcer. Method: A scoping review was conducted following the Arksey and O’Malley framework. Literature searches were performed in electronic databases (PubMed and Google Scholar) for studies published within the last five years. Eligible articles were analyzed using descriptive and thematic approaches. Results: Most studies applied the Wagner classification as the primary clinical assessment tool, while SHID was reported to provide a more comprehensive depiction of wound conditions. Conclusion: A consistent association between wound severity and decreased quality of life was identified, although direct integration of both classifications with QoL instruments remains limited. Keywords: Diabetic Foot Ulcer; Wagner Classification; SHID; Quality of Life; Scoping Review.